Beginning Perl Web Development - Suehring, Steve (Apress, 2012)
This is a book about Perl, the programming language. More specifically, this is a book about some aspects of Perl interacting with the Internet. The book includes coverage of CGI through the Perl CGI.pm module, as well as much additional information. You’ll explore such topics as how to send e-mail from a Perl program through Net::SMTP, how to use Net::DNS, and even how to use Net::Ping. You’ll learn how to build a templated web site two different ways, one with the help of HTML::Mason and the other with the Template Toolkit. You’ll learn how to consume SOAP web services, how to read and write RSS, and how to work with XML, all through Perl.